Jupiter's wife - Negroponte, Michel; Morgan, Gabriel; Cogan, Maggie; Morales, Beo.; Williams, Brooks; Docurama (Firm); New Video Group ([United States] : Docurama ; New York, NY : Distributed by New Video Group, 2004)
This is the story of Maggie, a beguiling homeless woman living in New York City's Central Park. In her forties, Maggie's vibrant personality and unconventional persona attract attention since she has 6 dogs and carries a hugh backpack full of her personal belongings. A captivating jumble of cryptic stories, Maggie's conversations are laced with intriguing claims - including the claim that she is the daughter of actor Robert Ryan and that she is married to the Roman god Jupiter.
DVD, Region 1, full screen presentation; Dolby Digital stereo.
Interview with: Maggie Cogan.
Director of photography, Michel Negroponte ; editor, Michel Negroponte ; music, Beo Morales, Brooks Williams.
MPAA rating: Not rated.
Special features: never-before-seen scenes; filmmaker biography; filmmaker statement.
Keywords: Homeless women -- New York (State) -- New York; Central Park (New York, N.Y.); Women -- Social conditions; Women -- Health and hygiene; Women -- Mental health; Feature films; Documentary films